ANALISIS RESIKO MANUAL HANDLING DAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDS) DENGAN NORDIC BODY MAP (NBM) PADA UNIT PAVING BLOK UD.CAHAYA ANUGRAH - , Anggia Paramitha, Eka Rani , Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Work that is done manually handling is still found in the company. So we need a risk assessment of Manual Handling which has the potential to cause Musculoskeletal Disorders (MSDs) complaints in workers. This study aims to determine the level of risk of manual handling musculoskeletal disorders in employees of UD. Cahaya Anugrah Pekanbaru. The population in this study includes all workers at UD. Cahaya Anugrah Pekanbaru. Primary data was collected by using a quetionnaire as an instrument to prove the results of the study, to test the results of the questionnaire in this study using the Nordic Body Map (NBM) method. The sampling technique that has been selected is the total of the entire population (15 workers at UD. Cahaya Anugrah Pekanbaru). The results showed that : 1) there was a risk of manual handling on UD. Cahaya Anugrah Pekanbaru workers, 2) there was a risk of musculoskeletal disorders in UD. Cahaya Anugrah Pekanbaru workers. Keywords : Manual Handling, Musculoskeletal Disorders